Moving-mesh simulations of star-forming cores in magneto-gravo-turbulence - Mocz, Philip; Burkhart, Blakesley; Hernquist, Lars; McKee, Christopher F.; Springel, Volker (The astrophysical journal, 2017)
Star formation in our Galaxy occurs in molecular clouds that are self-gravitating, highly turbulent, and magnetized. We study the conditions under which cloud cores inherit large-scale magnetic field morphologies and how the field is governed by cloud turbulence. We present four moving-mesh simulations of supersonic, turbulent, isothermal, self-gravitating gas with a range of magnetic mean-field strengths characterized by the Alfvénic Mach number ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn1.gif] $ \mathcal M _\rmA,0$ , resolving prestellar core formation from parsec to a few astronomical unit scales. In our simulations with the turbulent kinetic energy density dominating over magnetic pressure ( ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn2.gif] $ \mathcal M _\rmA,0\gt 1$ ), we find that the collapse is approximately isotropic with B ∝ ρ 2/3 , core properties are similar regardless of initial mean-field strength, and the field direction on 100 au scales is uncorrelated with the mean field. However, in the case of a dominant large-scale magnetic field ( ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn3.gif] $ \mathcal M _\rmA,0=0.35$ ), the collapse is anisotropic with B ∝ ρ 1/2 . This transition at ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn4.gif] $ \mathcal M _\rmA,0\sim 1$ is not expected to be sharp, but clearly signifies two different paths for magnetic field evolution in star formation. Based on observations of different star-forming regions, we conclude that star formation in the interstellar medium may occur in both regimes. Magnetic field correlation with the mean field extends to smaller scales as ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn5.gif] $ \mathcal M _\rmA,0$ decreases, making future Atacama Large Millimeter Array observations useful for constraining ##IMG## [http://ej.iop.org/images/0004-637X/838/1/40/apjaa6475ieqn6.gif] $ \mathcal M _\rmA,0$ of the interstellar medium.